Glycyrrhetinic Acid Protects α-Naphthylisothiocyanate- Induced Cholestasis Through Regulating Transporters, Inflammation and Apoptosis - Yan, Miao; Guo, Lin; Yang, Yan; Zhang, Bikui; Hou, Zhenyan; Gao, Yue; Gu, Hongmei; Gong, Hui (Frontiers in Pharmacology, 2021)
Glycyrrhetinic acid (GA), the active metabolic product of Glycyrrhizin (GL) that is the main ingredient of licorice, was reported to protect against α-naphthylisothiocyanate (ANIT)- induced cholestasis. However, its protective mechanism remains unclear. In our work, the cholestatic liver injury in mice was caused by ANIT and GA was used for the treatment. We assessed cholestatic liver injury specific indexes, histopathological changes, bile acid transporters, inflammation and apoptosis. The results of liver biochemical index and histopathological examination showed that GA markedly attenuated ANIT-induced liver injury. Mechanism research suggested that GA could activate the expression of farnesoid x receptor (FXR) and its downstream bile acids transporters Na+/taurocholate co-transporting polypeptide (NTCP), bile salt export pump (BSEP) and multidrug resistance-associated protein 2 (MRP2), as well as the nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream proteins MRP3, MRP4. These transporters play a vital role in mediating bile acid homeostasis in hepatocytes. Moreover, GA could significantly inhibit the ANIT-induced activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) inflammatory pathway and the increase of tumor necrosis factor-α (TNF-α) concentration in serum. Also, GA protected against ANIT-induced mitochondrial apoptosis by regulating the expression of Bcl-2, Bax, cleaved caspase 3 and cleaved caspase 9. In conclusion, GA alleviates the hepatotoxicity caused by ANIT by regulating bile acids transporters, inflammation and apoptosis, which suggests that GA may be a potential therapeutic agent for cholestasis.